Allopurinol and Cardiovascular Outcomes in Adults With Hypertension. Issue 3 (March 2016) - MacIsaac, Rachael L.; Salatzki, Janek; Higgins, Peter; Walters, Matthew R.; Padmanabhan, Sandosh; Dominiczak, Anna F.; Touyz, Rhian M.; Dawson, Jesse
Abstract : Allopurinol lowers blood pressure in adolescents and has other vasoprotective effects. Whether similar benefits occur in older individuals remains unclear. We hypothesized that allopurinol is associated with improved cardiovascular outcomes in older adults with hypertension. Data from the United Kingdom Clinical Research Practice Datalink were used. Multivariate Cox-proportional hazard models were applied to estimate hazard ratios for stroke and cardiac events (defined as myocardial infarction or acute coronary syndrome) associated with allopurinol use over a 10-year period in adults aged >65 years with hypertension. A propensity-matched design was used to reduce potential for confounding. Allopurinol exposure was a time-dependent variable and was defined as any exposure and then as high (≥300 mg daily) or low-dose exposure. A total of 2032 allopurinol-exposed patients and 2032 matched nonexposed patients were studied. Allopurinol use was associated with a significantly lower risk of both stroke (hazard ratio, 0.50; 95% confidence interval, 0.32–0.80) and cardiac events (hazard ratio, 0.61; 95% confidence interval, 0.43–0.87) than nonexposed control patients. In exposed patients, high-dose treatment with allopurinol (n=1052) was associated with a significantly lower risk of both stroke (hazard ratio, 0.58; 95% confidence interval, 0.36–0.94) and cardiac events (hazard ratio, 0.65; 95% confidence interval, 0.46–0.93) than low-dose treatment (n=980). Allopurinol use is associated with lower rates of stroke and cardiac events in older adults with hypertension, particularly at higher doses. Prospective clinical trials are needed to evaluate whether allopurinol improves cardiovascular outcomes in adults with hypertension. Abstract : Supplemental Digital Content is available in the text.